Behavioral Economics Insights into Consumer Decision-Making in Online Marketplaces - Bagus Yunianto Wibowo (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study reveals the influence of psychological, social, and emotional factors on consumer decision-making in online marketplaces through a behavioral economics approach. Cognitive biases such as anchoring bias, herd behavior, and loss aversion play a significant role in purchasing decisions, while social factors, including product reviews, also influence consumer tendencies. Personalized recommendation and promotion algorithms have been shown to accelerate purchasing decisions, but challenges related to filter bubbles and data privacy need to be addressed. The study also highlights the importance of stricter regulation to protect consumers and prevent manipulation. These findings open up space for further research on the long-term impact of recommendation algorithms and cultural factors on consumer behavior in online marketplaces.